If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 2x + -6 = 4x Reorder the terms: -6 + -7x + 2x = 4x Combine like terms: -7x + 2x = -5x -6 + -5x = 4x Solving -6 + -5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -6 + -5x + -4x = 4x + -4x Combine like terms: -5x + -4x = -9x -6 + -9x = 4x + -4x Combine like terms: 4x + -4x = 0 -6 + -9x = 0 Add '6' to each side of the equation. -6 + 6 + -9x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -9x = 0 + 6 -9x = 0 + 6 Combine like terms: 0 + 6 = 6 -9x = 6 Divide each side by '-9'. x = -0.6666666667 Simplifying x = -0.6666666667
| -8+v=3v-v | | 3c+10=25 | | 3(7+x)=4-(5+2x) | | -5(5)-5y=25 | | 8.5*3=33.5 | | 156=-4-8b | | 8*63=8*n+8*3 | | 13(4c-5)=8c-4 | | Ax=1+4x | | v^2-8v=-12 | | -1+2n-3+4n=2-6n+6n | | 4x+2=8+x | | x^3-4x^2+2x-6=0 | | 33=9+4n | | 9=b/4+7 | | 15x^22+7x-2=0 | | 11y-4(3+3y)=3-3(4-y) | | 5=-8(5+3a)-3(-7-7a) | | -99=12(x+3)+6x | | y+5=2y+3 | | -3(p-4)+6(-1+7p)=-72 | | -6+9y=12 | | 2x+2(2x+5)=6x+3+7 | | -29=-5(n-1)+6(7+4n) | | 7n+6=4n-5 | | -3v-9=-6 | | -6x+y=-4.5 | | -60=-8(1+5m)-2(m+5) | | x=4(6)+5 | | 2d-4=11+4d-2d | | 5=y-3m | | 10v^2+66v-28=0 |